The New CLOCIT Irradiation Facility for 40Ar/39Ar Geochronology: Characterisation, Comparison with CLICIT and Implications for High‐Precision Geochronology. Issue 3 (4th June 2018) - Rutte, Daniel; Becker, Tim A.; Deino, Alan L.; Reese, Steven R.; Renne, Paul R.; Schickler, Robert A.
Abstract : The Cadmium‐Lined Outer‐Core Irradiation Tube (CLOCIT) is a new irradiation facility for 40 Ar/ 39 Ar geochronology at the Oregon State University TRIGA ® reactor. We report fluence (i.e., time‐integrated flux) parameters from the first four CLOCIT irradiations and compare them with the existing Cadmium‐Lined Inner‐Core Irradiation Tube (CLICIT). CLOCIT provides an average neutron flux equivalent of 1.45–1.53 × 10 −4 J  h −1 ; about 55% of CLICIT. Radial fluence gradients were on the order of 0.2–4.2% cm −1 . A planar fit of J ‐values results in residuals in the range of uncertainty in the J ‐value, but systematic deviations resolve a non‐planar component of the neutron flux field, which has also been observed in CLICIT. Axial neutron fluence gradients were 0.6–1% cm −1, compared with 0.7–1.6% cm −1 for the CLICIT. Production rate ratios of interfering reactions were ( 40 Ar/ 39 Ar)K  = (4 ± 6) × 10 −4 and ( 38 Ar/ 39 Ar)K  = (1.208 ± 0.002) × 10 −2, ( 36 Ar/ 37 Ar)Ca  =  (2.649 ± 0.014) × 10 −4, ( 38 Ar/ 37 Ar)Ca  =  (3.33 ± 0.12) × 10 −5 and ( 39 Ar/ 37 Ar)Ca  =  (9.1 ± 0.28) × 10 −4, similar to the CLICIT values. Key Points: The new CLOCIT irradiation facility for 40 Ar/ 39 Ar geochronology provides 55% of the flux of CLICIT with similar production rate ratios for interfering reactions. Radial fluence gradients in CLOCIT vary between irradiations ranging 0.2–4.2% cm −1 . The non‐planar component of the fluence field can be resolved in CLOCIT and CLICIT and is significant for high‐precision geochronology .